Professional communication in audiology - Ramachandran, Virginia; Stach, Brad A. (Plural Publishing, Inc., 2013)
Provides students of audiology and practicing clinicians with a global framework for understanding the role of communication in audiologic practice, as well as practical strategies for implementation of communication principles in a clinical setting.